2 x + ( 0 . 5 ) 2 x − 3 − 6 ( 0 . 5 ) x = 1
How many real values of x satisfy the equation above?
Bonus question: Determine the value(s) of x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did exactly the same :D
This is a very silly question but would you explain why the exponents weren't used for 1? as in 0.5 has been broken down to 1/2 bu only on 2 the exponent is used? I hope my question is understandable :P
Log in to reply
For all real x , 1 x = 1 . So, for example,
( 0 . 5 ) x = ( 2 1 ) x = 2 x 1 x = 2 x 1
:)
Problem Loading...
Note Loading...
Set Loading...
2 x + ( 0 . 5 ) 2 x − 3 − 6 ( 0 . 5 ) x 2 x + 2 2 x − 3 1 − 6 ⋅ 2 x 1 2 x + 2 2 x 8 − 6 ⋅ 2 x 1 2 3 x + 8 − 6 ⋅ 2 x 2 3 x − 2 2 x − 6 ⋅ 2 x + 8 = 1 = 1 = 1 = 2 2 x = 0 Letting y = 2 x , the last equation becomes y 3 − y 2 − 6 y + 8 = 0 By synthetic division, we find that y = 2 is a root. The reduced equation thus becomes y 2 + y − 4 = 0 , and by quadratic formula, the two other values are y = 2 − 1 ± 1 7 .
However, take note that we have the substitution y = 2 x , thus y ≥ 0 for all x . Hence, the value y = 2 − 1 − 1 7 is not acceptable.
Thus, there are only 2 values of x that satisfy the equation. These are y = 2 x = 2 ⟹ x = 1 and y = 2 x = 2 − 1 + 1 7 ⟹ x = lo g 2 2 − 1 + 1 7